Acrylamide and glycidamide hemoglobin adduct levels and endometrial cancer risk: A nested case‐control study in nonsmoking postmenopausal women from the EPIC cohort. Issue 5 (1st October 2015) - Obón‐Santacana, Mireia; Freisling, Heinz; Peeters, Petra H.; Lujan‐Barroso, Leila; Ferrari, Pietro; Boutron‐Ruault, Marie‐Christine; Mesrine, Sylvie; Baglietto, Laura; Turzanski‐Fortner, Renee; Katzke, Verena A.; Boeing, Heiner; Quirós, J. Ramón; et al.
Abstract : Acrylamide, classified in 1994 by IARC as "probably carcinogenic to humans, " was discovered in 2002 in some heat‐treated, carbohydrate‐rich foods. Four prospective studies have evaluated the association between dietary acrylamide intake and endometrial cancer (EC) risk with inconsistent results. The purpose of this nested case‐control study, based on the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, was to evaluate, for the first time, the association between hemoglobin adducts of acrylamide (HbAA) and glycidamide (HbGA) and the risk of developing EC in non‐smoking postmenopausal women. Hemoglobin adducts were measured in red blood cells by HPLC/MS/MS. Four exposure variables were evaluated: HbAA, HbGA, their sum (HbAA+HbGA), and their ratio (HbGA/HbAA). The association between hemoglobin adducts and EC was evaluated using unconditional multivariable logistic regression models, and included 383 EC cases (171 were type‐I EC), and 385 controls. Exposure variables were analyzed in quintiles based on control distributions. None of the biomarker variables had an effect on overall EC (HRHbAA;Q5vsQ1 : 0.84, 95%CI: 0.49–1.48; HRHbGA;Q5vsQ1 : 0.94, 95%CI: 0.54–1.63) or type‐I EC risk. Additionally, none of the subgroups investigated (BMI < 25 vs . ≥25 kg m −2, alcohol drinkers vs . never drinkers, oral contraceptive users vs . non‐users) demonstrated effect measure modification. Hemoglobin adducts of acrylamide or glycidamide were not associated with EC or type‐I EC risk in 768 nonsmoking postmenopausal women from the EPIC cohort. Abstract : What's new? Acrylamide in food may not lead to endometrial cancer, according to a new report. The carcinogen has provoked public concerns because it can be detected in certain foods. Prospective studies on the relationship between endometrial cancer and dietary acrylamide, however, have produced conflicting results. Taking a different tack, these authors conducted a case‐control study, drawing on data from the European Prospective Investigation into Cancer and Nutrition (EPIC). They measured the amounts of certain compounds formed by hemoglobin with acrylamide or glycidamide in nonsmoking, postmenopausal women. Neither of these levels, they report, had any impact on endometrial cancer risk.